A new record of Neoperla obliqua Banks, 1930 (Plecoptera: Perlidae) from Mt. Malindang, Mindanao, Philippines and association of life stages using DNA barcodes - Cruz, Ian Niel B. Dela; Nuñeza, Olga M.; Lin, Chung-Ping (Zootaxa, 2018)
The nymph of the perlid Neoperla obliqua Banks, 1913 from Mt. Malindang, Mindanao Island, the Philippines is described and associated with the male and female adults using DNA barcodes. Using pairwise CO1, the nymph was associated with 99.9 ± 0.14% interspecific similarity, while comparison between sexes generated a 0.2% intraspecific divergence between males and females of putative conspecifics. Additionally, the mature ova from female adults are described using scanning electron microscopy (SEM). The distinctive chorionic surface is rugose with longitudinal ridge-like pattern with a bare and flat collar.